In vitro infection with dengue virus induces changes in the structure and function of the mouse brain endothelium (2015)
Background The neurological manifestations of dengue disease are occurring with greater frequency, and currently, no information is available regarding the reasons for this phenomenon. Some viruses infect and/or alter the function of endothelial organs, which results in changes in cellular function, including permeability of the blood-brain barrier (BBB), which allows the entry of infected cells or free viral particles into the nervous system. Methods In the present study, we standardized two in vitro models, a polarized monolayer of mouse brain endothelial cells (MBECs) and an organized co-culture containing MBECs and astrocytes. Using these cell models, we assessed whether DENV-4 or the neuro-adapted dengue virus (D4MB-6) variant infects cells or induces changes in the structure or function of the endothelial barrier. Results The results showed that MBECs, but not astrocytes, were susceptible to infection with both viruses, although the percentage of infected cells was higher when the neuro-adapted virus variant was used. In both culture systems, DENV infection changed the localization of the tight junction proteins Zonula occludens (ZO-1) and Claudin-1 (Cln1), and this process was associated with a decrease in transendothelial resistance, an increase in macromolecule permeability and an increase in the paracellular passing of free virus particles. MBEC infection led to transcriptional up-regulation of adhesion molecules (VCAM-1 and PECAM) and immune mediators (MCP-1 and TNF- α) that are associated with immune cell transmigration, mainly in D4MB-6-infected cells. Conclusion These results indicate that DENV infection in MBECs altered the structure and function of the BBB and activated the endothelium, affecting its transcellular and paracellular permeability and favoring the passage of viruses and the transmigration of immune cells. This phenomenon can be harnessed for neurotropic and neurovirulent strains to infect and induce alterations in the CNS.